2014
DOI: 10.3389/fpsyg.2014.00728
|View full text |Cite
|
Sign up to set email alerts
|

Forgiving, fast and slow: validity of the implicit association test for predicting differential response latencies in a transgression-recall paradigm

Abstract: This study examined the role of automaticity in forgiving a real-life offense. As an alternative to self-report, an Implicit Association Test (IAT) of forgiveness was developed. Implicit (IAT-measured) and explicit (self-reported) forgiveness predicted shorter response times of state forgiveness ratings. The forgiveness IAT was highly reliable, moderately stable over time, and demonstrated incremental validity. Results suggest that the newly introduced forgiveness IAT could advance personality research beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…Fifth, in the agreeableness domain, as much evidence is observed in favour of (Banse et al, , Studies 1 and 3), as against (Banse et al, , study 2; Schnabel et al, ) the expected differential correlation of implicit and explicit measures with social desirability. In none of the four studies, a differential correlation was found with impression management (Banse et al, , study 3; LaBouff, Rowatt, Johnson, Tsang, & McCullough Willerton, , Study 3; Rowatt et al, , Study 1; Fatfouta, Schöder‐Abé, & Merkl, ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fifth, in the agreeableness domain, as much evidence is observed in favour of (Banse et al, , Studies 1 and 3), as against (Banse et al, , study 2; Schnabel et al, ) the expected differential correlation of implicit and explicit measures with social desirability. In none of the four studies, a differential correlation was found with impression management (Banse et al, , study 3; LaBouff, Rowatt, Johnson, Tsang, & McCullough Willerton, , Study 3; Rowatt et al, , Study 1; Fatfouta, Schöder‐Abé, & Merkl, ).…”
Section: Resultsmentioning
confidence: 98%
“…The results of this study demonstrated that the predictive influence of the angriness IAT on negative social feedback—but not on performance feedback—got weaker as the working memory capacity increased. A forgiveness IAT only predicted the time a participant needed to rate his feelings of revenge (not avoidance and benevolence; Fatfouta et al, ). This predictive relation was still observed when the directly measured tendency to forgive was controlled for.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We fixed the order of the blocks (i.e., all participants started with the pro-Flemish block) because we were interested primarily in interindividual differences in RRT scores, that is, we wanted to correlate RRT scores with other measures. Counterbalancing block order is known to increase error variance (i.e., differences in scores between participants might reflect not only differences in the to-be-measured attribute but also differences in block order) and thus to lower correlations (see Perugini and Banse, 2007 , for a discussion and the recommendation to fix block order). Because there are few studies about the effect of block order on the validity of implicit measures (e.g., studies examining whether correlations with validity criteria are stronger when starting with an attitude-inconsistent vs. an attitude-consistent block), we did not have strong reasons to select one of the two block orders but more or less randomly decided to always start with the pro-Flemish block.…”
mentioning
confidence: 99%
“…Based on the speed of reaction to the stimuli, we argue that the patterns observed here are unmediated and indicative of implicit attitudes. The method that we have chosen in our study has shown repeatedly that individuals process information implicitly (i.e., automatically or unconsciously) (Greenwald and Banaji, 1995;Bargh and Chartrand, 1999;Banaji, 2001;Greenwald et al, 2002Greenwald et al, , 2009Fatfouta et al, 2014) as opposed to explicitly (controlled or conscious). To be more precise, we argue that our results show attitudes below the level of consciousness due to three different aspects related to the IAT method.…”
Section: Summary and Discussionmentioning
confidence: 99%